If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying c + -7 = 3c + -33 Reorder the terms: -7 + c = 3c + -33 Reorder the terms: -7 + c = -33 + 3c Solving -7 + c = -33 + 3c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-3c' to each side of the equation. -7 + c + -3c = -33 + 3c + -3c Combine like terms: c + -3c = -2c -7 + -2c = -33 + 3c + -3c Combine like terms: 3c + -3c = 0 -7 + -2c = -33 + 0 -7 + -2c = -33 Add '7' to each side of the equation. -7 + 7 + -2c = -33 + 7 Combine like terms: -7 + 7 = 0 0 + -2c = -33 + 7 -2c = -33 + 7 Combine like terms: -33 + 7 = -26 -2c = -26 Divide each side by '-2'. c = 13 Simplifying c = 13
| x^2-4*x=10 | | 33x=5(3x+18) | | 18p-53=4p+17 | | 6z^2-9=46 | | -13=-5m | | (7-v)(2v+3)=0 | | 21x=3x+18 | | 4y+2=3y+11 | | -3.1a=7.75 | | Y-3=-3y-4e | | x+x+1000=86000 | | -15=-8(2x+7) | | 17x=5x+12 | | 6.4x+4=5.4x | | 7w=5w+6 | | 54=18-9x | | 67b=98.2 | | 5y-3=3y+27 | | (X^3y^5)(-y^7x)= | | 6x^2+3x-46=0 | | -8n+5+7=-27 | | 9x-65=2x+40 | | 0.79t+24=1.19 | | 4a^3=44a^2 | | X+15+81=180 | | 8x+3=9-5x | | -1x=-2x-1 | | 9r-6=8r+3 | | tan*x=0.12704918 | | -4(5z-6)=24+8z | | 2c+4c=4 | | .52=log(x) |